Perancangan dan Pembuatan Aplikasi Pepak Basa Jawa Menggunakan MobiOne Studio - Anglila Nayanggita; Kodrat Iman Satoto; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Indonesia is a nation that has a diversity of cultures and the arts, one of which is Javanese language. Javanese language is a heritage that should be preserved because it is still taught in schools and used in everyday life. The main book to learn Javanese language is Pepak Basa Jawa; a book that contains the essence of Javanese language. The rapid increase of technological development provides easiness for people, especially the pressence of gadgets. Therefore, the making of Pepak Basa Jawa in an application it needed to be a learning media to learn and conserve Javanese language for Indonesian people. The application is practically and attractively packed through iOS based mobile devices. Application Pepak Basa Jawa is built using MobiOne Studio software. Multimedia development method used is the Multimedia Development Life Cycle (MDLC) which consists of six stages: concept, design, collection of material, manufacture, testing, and distribution. The Black Box test is used for application testing method. The results of this study is in the form of an application named Pepak Basa Jawa that can run well on mobile devices based on iOS. This application can be an alternative for the people of Indonesia as a medium of learning in learning the Javanese language.